The impact of innovation on employment in Europe: An analysis using CIS data - Doris Blechinger; Alfred Kleinknecht; Georg Licht; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1998)
Technological progress in western economies has contributed to an immense rise in productivity, incomes and goods available over the last hundred years. Though not to the same extent as productivity and wages, population and employment have risen as well. Nevertheless, innovations are often blamed for job destruction and unemployment, with workers historically fighting against technological progress. The impact of innovation on employment today is not as clearcut as it used to be in times of the first factory or the first railroad. The pace of technological progress in an open world economy has accelerated compared to former times, resulting in a greater number of product and process innovations as well as processes related to these product and process innovations. The evolutionary nature of a dynamic, growing market economy results in the perpetual birth and death of firms and the perpetual creation and destruction of jobs -all within a single industry all at the same time.
Keywords: 330